Interest Rate Policy Moderate The Performance Impact On Banking Stock Price In Indonesia - Sari, Laynita; Assagaf, Aminullah; Lusiana, Lusiana; Elfiswandi, Elfiswandi; Zefriyeni, Zefriyeni (International Journal of Artificial Intelligence Research, 2024)
The stock price is a factor that investors must consider in investing. The stock price is an indicator of the successful management of the company. An increase in share price will reflect an increase in shareholder wealth as an investor. There is a phenomenon in banking stock prices in Indonesia from 2020-2021, where share prices have decreased yearly. This study aimed to investigate the effect of company performance on stock prices by using interest policy as a moderating variable. The method used in this research is panel data regression. The results show that performance positively affects stock prices, and interest policy moderates the relationship between performance and stock prices.